MENINGKATNYA KASUS LGBT DI INDONESIA - Indah Permata Sari (Civilia: Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2023)
This research is motivated by the existence of LGBT (Lesbian, Gay, Bisexual, and Transgender) people in Indonesia. Some people see that LGBT people violate eastern religious norms, laws, and customs. Others feel that LGBT people should be protected and recognized by the state on the basis of their rights